3
$\begingroup$

For a conservative force $\vec{F}(x,y)$ we have $$\vec{F}(x,y) = - \vec{\nabla}\phi(x,y)$$ where $\phi(x,y)$ is a potential function for $\vec{F}(x,y)$.

Again, Newton's second law states that $$ \vec{F}(t) = \frac{d \vec{P}(t)}{dt}$$ where $\vec{P}(t)$ is the momentum.

How these two equations are compatible; i.e, for a conservative force $\vec{F}(x,y)$ how can we write the Newton's second law?

Edit

For a conservative force $\vec{F}(x,y)$ how can we write the Newton's second law?

$\endgroup$
  • 2
    $\begingroup$ A particle at position $\vec{x}(t)$ at time $t$ will experience a force $F(t)=-\vec{\nabla}\phi(\vec{x}(t))$. $\endgroup$ – lemon Oct 2 '14 at 11:13
  • $\begingroup$ I don't understand what you are asking...in what sense do you think there is a problem of "compatibility" if you write $\dot{p}=-\nabla\phi$? $\endgroup$ – yuggib Oct 2 '14 at 11:37
  • $\begingroup$ @yugib: I have edited the question. $\endgroup$ – rainman Oct 2 '14 at 11:39
  • $\begingroup$ You edited the question so that the last line is exactly repeated. Why do you expect that this will clarify the question? $\endgroup$ – Jim Oct 2 '14 at 13:40
  • $\begingroup$ @Jim: Yes, you are right. I should have posed the question in a different way as it clarifies the query. $\endgroup$ – rainman Oct 2 '14 at 14:35
3
$\begingroup$

What @lemon said is right. While $\bf F = -\nabla \phi\left({\bf r}\right)$ suggests that $\bf F$ depends on $\bf r$, it ultimately depends on time through ${\bf r} = {\bf r}\left(t\right)$. That is, ${\bf F} = -\nabla \phi\left({\bf r}\left(t\right)\right)$. So, there is no inconsistency in writing Newton's second law as (a dot represents a time derivative) $$ {\bf F} = m \ddot{\bf r} = -\nabla \phi $$ In fact, we don't have to restrict ourselves to a conservative force. $\bf F$ can depend on position, velocity, and time explicitly, ${\bf F} = {\bf F}\left({\bf r}\left(t\right),\dot{\bf r}\left(t\right),t\right)$, since you will end up with a perfectly consistent system of differential equations $$ \begin{eqnarray} \ddot{x} &=& F_x\left(x,y,z,\dot{x},\dot{y},\dot{z},t\right)/m \\ \ddot{y} &=& F_y\left(x,y,z,\dot{x},\dot{y},\dot{z},t\right)/m \\ \ddot{z} &=& F_z\left(x,y,z,\dot{x},\dot{y},\dot{z},t\right)/m \\ \end{eqnarray} $$ To work a simple example, consider the potential energy $$ \phi\left(x\right) = \frac{1}{2} k x^2. $$ Then $$ {\bf F} = -\nabla\left(\frac{1}{2} k x^2\right) = -k x \ \hat{\bf x} = m \left(\ddot{x} \ \hat{\bf x} + \ddot{y} \ \hat{\bf y} + \ddot{z} \ \hat{\bf z}\right), $$ or $$ \begin{eqnarray} m \ddot{x} = -kx &\Rightarrow& x\left(t\right) = x\left(0\right) \cos\left(\omega t \right) + \frac{\dot{x}\left(0\right)}{\omega} \sin\left(\omega t\right), \omega = \sqrt{k/m} \\ m \ddot{y} = 0 &\Rightarrow& y\left(t\right) = {\dot y}\left(0\right) t + y\left(0\right)\\ m \ddot{z} = 0 &\Rightarrow& z\left(t\right) = {\dot z}\left(0\right) t + z\left(0\right)\\ \end{eqnarray} $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.